Protective role of Roflumilast against cadmium-induced cardiotoxicity through inhibition of oxidative stress and NF-κB signaling in rats - Mohd Nazam Ansari; Majid A. Ganaie; Najeeb Ur Rehman; Khalid M. Alharthy; Tajdar H. Khan; Faisal Imam; Mushtaq A. Ansari; Naif O. Al-Harbi; Basit L. Jan; Ishfaq A. Sheikh; Abubaker M. Hamad (Elsevier, 2019)
Cadmium (Cd), a potent cardiotoxic environmental heavy metal, induces oxidative stress and membrane disturbances in cardiac myocytes. Phosphodiesterase (PDEs) retards the positive inotropic effects of β-adrenoceptor activation by decreasing levels of cAMP via degradation. Hence, PDE inhibitors sensitize the heart to catecholamine and are therefore, used as positive inotropic agents. The present study was designed to probe the potential attenuating effects of the selective PDE4 inhibitor (Roflumilast, ROF), on cardiac biomarkers, lipid profile, lipid peroxidation products, antioxidant status and histology of cardiac tissues against Cd-induced cardiotoxicity in rats. Rats were randomly distributed into four different groups: group 1, served as the normal control group. Group 2, served as the toxic control group and were administered Cd (3 mg/kg, i.p.) for next 7 days. Groups 3 and 4, served as treatment groups that received Cd with concomitant oral administration of ROF doses (0.5 and 1.5 mg/kg), respectively for 7 days. Serum samples of toxic control group rats resulted in significant (P < 0.001) increase in lactate dehydrogenase (LDH), creatine phosphokinase (CPK), total cholesterol (TC), triglycerides (TG) and low density lipoproteins (LDL) levels with concomitant decrease in high density lipoproteins (HDL) levels in serum which were found reversed with both of ROF treatment groups. Cd also causes significant increased (P < 0.001) in myocardial malondialdehyde (MDA) contents while cardiac glutathione (GSH) level, superoxide dismutase (SOD) and catalase (CAT) enzyme activities were found decreased whereas both doses of ROF, significantly reversed these oxidative stress markers and antioxidant enzymes. Cardiotoxicity induced by Cd also resulted in enhanced expression of non-phosphorylated and phosphorylated form of NF-κB p65 and decreased expression of glutathione-S-transferase (GST) and NQO1 which were found reversed with ROF treatments, comparable to normal control group. Histopathological changes were also improved by ROF administration as compared to Cd treated rats alone. In conclusion, Roflumilast exhibited attenuating effect against Cd-induced cardiac toxicity. Keywords: Cadmium, Cardiotoxicity, CRF, GST, NF-κB, NQO1, Roflumilast